Cambridge o level biology revision guide (second edition) - Burton, Ian J. (Cambridge University Press Cambridge, United Kingdom, 2015)
Revision Guide to support students of Cambridge O Level Biology through their course and help them to prepare for assessment. The Cambridge O Level Biology Revision Guide supports students through their course, containing specifically designed features to help students apply their knowledge in their Cambridge O Level Biology (5090) exams. Containing up to date material that matches the syllabus for examination from 2017 and packed full of guidance such as Task boxes that contain questions and activities, Notes and Points to Remember throughout to help students to hone their revision and exam technique and avoid common mistakes. Written in a clear and straightforward tone, this Revision Guide is perfect for international learners.